2022
DOI: 10.1002/msc.1617
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and activity management education for individuals with systemic sclerosis: Adaptation and feasibility study of an intervention for a rare disease

Abstract: Purpose Fatigue is an overlooked symptom for musculoskeletal diseases, including rare conditions like systemic sclerosis (SSc). The purpose of this study were the following: (1) to adapt the content and delivery method of an existing fatigue intervention, and (2) to determine the feasibility of Fatigue and Activity Management Education in Systemic Sclerosis (FAME‐iSS). Methods In Phase 1 adaptations were recorded using the Framework for Modification and Adaptations. In Phase 2, participants completed the 6‐wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Similar to previous SSc studies (7,8), the current study found that fatigue and pain severity was associated with decreased social participation and physical function. Although intervention programs currently help to manage and reduce fatigue (17,18), fatigue's impact on cognitive function and reduced daily life activities remains problematic in people with SSc. Participants with higher levels of pain reported lower levels of social participation and physical function, consistent with previous SSc research (7,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previous SSc studies (7,8), the current study found that fatigue and pain severity was associated with decreased social participation and physical function. Although intervention programs currently help to manage and reduce fatigue (17,18), fatigue's impact on cognitive function and reduced daily life activities remains problematic in people with SSc. Participants with higher levels of pain reported lower levels of social participation and physical function, consistent with previous SSc research (7,23).…”
Section: Discussionmentioning
confidence: 99%
“…Although therapy and medical treatments can alleviate some clinical disease manifestations, patients with SSc face challenges in self-managing symptoms (14,15). No cure exists for SSc, but self-management programs can minimize the impact of the disease and optimize physical and psychological health (16)(17)(18)(19)(20). Despite these efforts, evidence suggests that cognitive impairment is a significant although understudied part of symptom experience in patients with SSc (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Moving from an in-person mode of delivery to an online platform was reported as beneficial especially for those working full time or living in rural and remote communities (Butzner & Cuffee, 2021;Carandang et al, 2022;Depuccio et al, 2022). Additionally, telehealth was recommended as a mode of delivery for patient education for IA care (De Thurah et al, 2022;Zangi et al, 2015).…”
Section: Individual Work-based Rehabilitation Interventions Focussing Onmentioning
confidence: 99%
“…However, many interventions do not address fatigue specifically and therefore may not include work‐specific fatigue management strategies. Furthermore, majority of these interventions are mainly individually delivered but some individuals with IA have reported the benefits of peer‐support in applying self‐management strategies (Carandang et al., 2022; O’Riordan et al., 2017). In response to preferences for group‐based interventions, a four‐week group‐based fatigue management programme, Fatigue and Activity Management Education for Work (FAME‐W), was developed.…”
Section: Introductionmentioning
confidence: 99%
“…Other interventions include Resilience-based, Energy Management to Enhance Wellbeing and Fatigue (RENEW) for systemic sclerosis; Reinvent, Integrate, Strengthen, Expand Self-Management Program (RISE) for cancer survivors (Goodfellow et al, 2021); and Reducing Arthritis Fatigue (RAFT) for arthritis (Hewlett et al, 2019). Others, such as Fatigue and Activity Management Education (FAME), were developed initially for one population (systemic lupus erythematosus; O’Riordan et al, 2017) and adapted for other groups such as systemic sclerosis (Carandang et al, 2022) and COVID. Although the evidence for occupational therapy’s role in fatigue management ranges in strength from moderate to strong, several limitations remain, and efforts must be made to advance this body of evidence.…”
mentioning
confidence: 99%